Avicenna and Thomas Aquinas on the possibility of talking about god - Az, Mehmet Ata (Bursa İlahiyat Foundation, 2013)
The most important claim of the thesis of the divine simplicity is that the daily expressions of language, which are constructed in reference to the material and composite beings, are not deep enough in the meaning, to the degree that one may not directly use them when talk- ing about God. This claim, which is about the meaning mode of ref- erences to God and the insufficiency of the form of reference, has brought about the problem of what sort of language must be used when talking about God. This study addresses the question of what kind and to what degree the resemblance of the caused beings to the final cause (God) - a resemblance that they possess in their natures - allows human beings to talk about the final cause. While the study presents an analysis of the views of Avicenna and Aquinas on talking about God, examining the differences and similarities between them, it will not give a detailed account of their dispute on the distinction between essence and existence in God. © Bursa İlahiyat Foundation.
Keywords: Aquinas; Attribute; Avicenna / Ibn Sina; Dhat; Essence; God; Tashkik and analogia